2021
DOI: 10.3389/fbioe.2021.801489
|View full text |Cite
|
Sign up to set email alerts
|

On the Effect of Soft Molecularly Imprinted Nanoparticles Receptors Combined to Nanoplasmonic Probes for Biomedical Applications

Abstract: Soft, deformable, molecularly imprinted nanoparticles (nanoMIPs) were combined to nano-plasmonic sensor chips realized on poly (methyl methacrylate) (PMMA) substrates to develop highly sensitive bio/chemical sensors. NanoMIPs (dmean < 50 nm), which are tailor-made nanoreceptors prepared by a template assisted synthesis, were made selective to bind Bovine Serum Albumin (BSA), and were herein used to functionalize gold optical nanostructures placed on a PMMA substrate, this latter acting as a slab wavegui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 71 publications
(107 reference statements)
0
9
0
Order By: Relevance
“…Here, we explored for the first time the effect of coupling nanogels to a POF plasmonic probe as a modification aspect of a state-of-the-art coupling of SPR POF probes with molecularly imprinted nanoparticles (nanoMIPs), synthetic polymeric receptors optimized for recognizing a target analyte using template-assisted synthesis and [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, we explored for the first time the effect of coupling nanogels to a POF plasmonic probe as a modification aspect of a state-of-the-art coupling of SPR POF probes with molecularly imprinted nanoparticles (nanoMIPs), synthetic polymeric receptors optimized for recognizing a target analyte using template-assisted synthesis and [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Nanogels were coupled to the POF, as described in [16]. A SAM was formed by incubating the gold POF surface in a 300 µM (R)-(+)-α-lipoic acid in ethanol 8% v/v solution overnight.…”
Section: Preparation Of the Nanogel-pof Platformmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the sensing systems were successfully applied for detection of HTR in (10 6 times) diluted serum mimic and human serum, 72 more applied work of developed plasmonic devices operating in complex biofluids is needed. Still, these works demonstrated that soft nanoMIPs can be promising receptors for improved protein analysis by active plasmonics 72,73,98 or MALDI-TOF-MS 99 and can bring in new opportunities to the MIP biosensing field. The scientific community is currently making efforts to come up with new synthetic procedures to prepare nanocomposites with efficient Raman enhancement.…”
Section: ■ Epitope Imprintingmentioning
confidence: 99%
“…In the past, researchers have exploited other advanced techniques to address different drawbacks of NAT-and molecular-based detection methods. These techniques include electrochemical [9,10], quartz crystal microbalance (QCM) [11,12], surface acoustic waves (SAW) [13], surface plasmon resonance/imaging (SPR(i)) [14,15], optical fiber [16], and surface-enhanced Raman spectroscopy (SERS) [17] that have been developed for the detection of viral infections. Table 1 also lists the existing sensor methods for COVID-19 diagnosis.…”
Section: Introductionmentioning
confidence: 99%